Pre-existing neutralizing antibody mitigates B cell dysregulation and enhances the Env-specific antibody response in SHIV-infected rhesus macaques - Jaworski, Juan Pablo (PLoS One, 2017)
Our central hypothesis is that protection against HIV infection will be powerfully influenced by the magnitude and quality of the B cell response. Although sterilizing immunity, mediated by pre-formed abundant and potent antibodies is the ultimate goal for B cell-targeted HIV vaccine strategies, scenarios that fall short of this may still confer beneficial defenses against viremia and disease progression. We evaluated the impact of sub-sterilizing pre-existing neutralizing antibody on the B cell response to SHIV infection. Adult male rhesus macaques received passive transfer of a sub-sterilizing amount of polyclonal neutralizing immunoglobulin (Ig) purified from previously infected animals (SHIVIG) or control Ig prior to intra-rectal challenge with SHIV(SF162P4) and extensive longitudinal sampling was performed. SHIVIG treated animals exhibited significantly reduced viral load and increased de novo Env-specific plasma antibody. Dysregulation of the B cell profile was grossly apparent soon after infection in untreated animals; exemplified by a ≈50% decrease in total B cells in the blood evident 2–3 weeks post-infection which was not apparent in SHIVIG treated animals. IgD+CD5+CD21+ B cells phenotypically similar to marginal zone-like B cells were highly sensitive to SHIV infection, becoming significantly decreased as early as 3 days post-infection in control animals, while being maintained in SHIVIG treated animals, and were highly correlated with the induction of Env-specific plasma antibody. These results suggest that B cell dysregulation during the early stages of infection likely contributes to suboptimal Env-specific B cell and antibody responses, and strategies that limit this dysregulation may enhance the host’s ability to eliminate HIV.